Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work &Amp; Social Computing 2016
DOI: 10.1145/2818048.2820071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensemaking Translucence on Distributed Collaborative Analysis

Abstract: Collaborative sensemaking requires that analysts share their information and insights with each other, but this process of sharing runs the risks of prematurely focusing the investigation on specific suspects. To address this tension, we propose and test an interface for collaborative crime analysis that aims to make analysts more aware of their sensemaking processes. We compare our sensemaking translucence interface to a standard interface without special sensemaking features in a controlled laboratory study.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Studies on display design have shown how variations in externalizations influence complex collaboration. For example, a translucent interface meant to assist sensemaking, fostered collaboration by supporting the sharing of insights and preventing narrowing of focus ( Goyal and Fussell, 2016 ). This led to collaborators identifying more problem solving clues as well as finding a target in a criminal investigation task.…”
Section: Cognition Technology and Teamsmentioning
confidence: 99%
“…Studies on display design have shown how variations in externalizations influence complex collaboration. For example, a translucent interface meant to assist sensemaking, fostered collaboration by supporting the sharing of insights and preventing narrowing of focus ( Goyal and Fussell, 2016 ). This led to collaborators identifying more problem solving clues as well as finding a target in a criminal investigation task.…”
Section: Cognition Technology and Teamsmentioning
confidence: 99%
“…The data visualisation pages focused on different themes, which aimed to spark discussion and exploration about potential relationships between government health expenditure, cancer, income and health risks. They explored: When all six tasks were finished the participants were asked to rate the usability of the interface using a SUS questionnaire [7,9], rate the workload required to complete the tasks using the raw NASA TLX questionnaire [16] and a collaboration questionnaire created by Goyal et al [14,15]. We used a between subject approach in order to accurately compare NASA TLX, collaboration questionnaire, SUS, and TCT scores.…”
Section: Methodsmentioning
confidence: 99%
“…Interactive technology provides effective support for users reflecting upon data in the process of sensemaking. Goyal et al [14] showed how implicit sharing can help users in sensemaking over a distance using a desktop interface. RAMPARTS [42] illustrated how mobile devices allowed for more effective sensemaking than a tabletop interface and Thaddeus [43] showed that effective interaction with information visualisation on tablets was possible.…”
Section: Data Exploration On Lhrds and Tabletsmentioning
confidence: 99%
“…This body of work has inspired later studies that looked at different aspects of sensemaking. In the context of EDA, recent work looked at how analysts manage uncertainty [7]; how they explore various types of alternatives [19]; and how groups deal with trade-offs [5] and build common ground [14]. The results of this body of work are often conceptual models, task taxonomies and design recommendations.…”
Section: Related Workmentioning
confidence: 99%